Clinicopathological features and prognostic significance of TAF1L in gastric cancer - Han Chen; Hang Chen; Jingquan Fang; Xingmao Huang; Xiu Zhu; Tengjiao Chai; Xiangliu Chen; Ling Huang; Pengfei Yu (BMC Gastroenterology)
Abstract Background TAF1L may play an important role in the occurrence and development of gastric cancer (GC), but the correlation between the expression of TAF1L and the clinicopathological factors and prognosis of GC is still unclear. Methods A total of 1053 GC patients in Zhejiang Cancer Hospital between January 1st, 2018 to December 31th, 2019 were screened. Finally, 120 patients met the inclusion criteria. TAF1L expression was detected by immunohistochemistry, and the correlations of TAF1L in clinicopathological characteristics and prognosis were analyzed. TCGA GC dataset was used to perform further bioinformatics analysis. Results In this study, TAF1L expression was evaluated in 120 clinical samples of GC. TAF1L expression was higher in tumor tissues and was associated with tumor differentiation (p = 0.046), signet-ring cells (p = 0.043), dMMR status (p = 0.011), lympho-vascular invasion (p = 0.038), and neural invasion (p = 0.005) in our cohort. Cases with high expression of TAF1L presented worse mean OS than those with low expression (40.3 months vs. 51.8 months, p = 0.019), and the difference was also significant in HER2-positive cases (20.9 months vs. 51.2 months, p = 0.007) as well as pMMR cases (38.8 months vs. 51.6 months, p = 0.006). Multivariate Cox regression analysis showed that TAF1L (HR = 2.044, 95%CI = 1.007–4.147, p = 0.048) and HER2 status (HR = 2.383, 95%CI = 1.087–5.222, p = 0.030) were independent prognosis factors of these patients. In subgroup analysis, TAF1L was the independent prognostic risk factor in HER2-positive patients (HR = 6.736, 95%CI = 1.373–33.032, p = 0.019). and pMMR patients (HR = 2.291, 95%CI = 1.126–4.660, p = 0.022). Besides, HER2 status was the independent prognostic risk factor in TAF1L-H patients (HR = 4.832, 95%CI = 1.908–12.239, p = 0.001). TCGA dataset also indicated the higher expression of TAF1L in tumors than normal tissues (p < 0.001). High TAF1L expression is linked to worse survival in MSS (11.0 months vs. 35.0 months, p = 0.0046) groups, and is negatively associated with overall survival in HER2-positive cases (24.0 months vs. 57.0 months, p = 0.0039). Conclusion TAF1L is closely related to the occurrence and development of GC. Our results suggested that TAF1L is a significant biomarker for predicting prognosis of GC and may play an important role in immunotherapy and targeted therapy.